VOKATIF PROFESI BAHASA SUNDA - wahya (Jurnal Kajian Budaya dan Humaniora, 2025)
ABSTRACT This study attempts to reveal the vocatives of Sundanese language professions from a morphological and syntactic perspective using a qualitative descriptive method. Data collection used a listening method with note-taking techniques. Data analysis used a morphological and syntactic approach. Data sources used four Sundanese language fiction books as samples, namely (1) Teu Tulus Paeh Nundutan/TTPN by Ki Umbara, 2013; (2) Oleh-Oleh Perang/OOP by Rukmana Hs. 2006; (3) Ki Merebot/KM by Ahmad Bakri, 2016; (4) Carita Nyi Halimah/CNH by Samsoedi, 2018. Based on the data source, there are nineteen professional vocative data found, which are divided into two forms, namely fifteen singular forms, namely (1) Guru 'Guru' (two data), (2) Dokter 'Doctor' (four data), (3) Suster 'Suster' (two data), (4) Mandor 'Mandor' (two data), and (5) Koki 'Koki' (one data) in the form of a whole word and (6) Dok 'Dok' (two data) and (7) Ndor 'Ndor' (two data) in the form of fragments. There are four combined professional vocatives: (8) Pa Mantri 'Pak Mantri' (three instances) and (9) Pa Supir 'Pak Supir' (one instance). Professional vocatives are found in declarative, imperative, interrogative, and exclamatory sentences, with 2, 2, 11, and 4 instances, respectively. Professional vocatives appear more frequently in interrogative sentences. They are positioned at the beginning of a sentence (initial), in the middle (medial), and at the end (final) (1, 1, and 17 instances, respectively). These professional vocatives are more frequently distributed at the end of a sentence. It can be concluded that Sundanese professional vocatives often appear in singular form as whole words in interrogative sentences at the end of the sentence. Keywords: professional vocatives; form; full word; fragment; distribution